Josiah's Reform in Judah 2 Kgs 22-23//2 Chr 34- 35 Implications for Nigeria in Pursuit of a Sustained Democracy - Olanisebe, Samson O. (2017)
Josiah was a young boy of eight years when he assumed the position of leadership over the Southern kingdom of Israel. Before his ascension to the throne, there were many structural defects in the kingdom. The immediate task before him was how to restructure and re-engineer the socio-religious decay he met on the ground, to which he responded promptly and with a record of success. This paper, therefore, through narrative analysis, identifies the leadership and followership qualities that assisted Josiah in his reform policy in Southern Israel and recommends, through content analysis, the imbibing of those qualities by the Nigerian leaders and citizenry in their quest for a sustained democracy.